2007
DOI: 10.1109/jsen.2007.894923
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Noninvasive Sensor for Driver Pulse Wave Measurement

Abstract: Noninvasive sensors to detect human physiological parameters are becoming more and more important. This is especially useful to monitor driver state as driver-vehicle system is a safety-critical system. Unfortunately, current technologies in these noninvasive sensors development are not satisfactory. In this research, we developed an intelligent integrated device called "smart wheel" to monitor drivers' physiology. Specifically, a group of polyvinylidene fluoride (PVDF) sensor, semiconductor temperature sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Instead of requiring the user to wear sensors, the product 'wears' the sensors in or on its body or surface. These sensors are typically found in input devices like computer mice (see Ji, 2007;Lin, 2011;Sun et al, 2014), or car steering wheels (Cai & Ling, 2007;Lin et al, 2007).…”
Section: Physiological Measuresmentioning
confidence: 99%
“…Instead of requiring the user to wear sensors, the product 'wears' the sensors in or on its body or surface. These sensors are typically found in input devices like computer mice (see Ji, 2007;Lin, 2011;Sun et al, 2014), or car steering wheels (Cai & Ling, 2007;Lin et al, 2007).…”
Section: Physiological Measuresmentioning
confidence: 99%
“…The gripping force on the steering wheel generally decreases when a driver becomes drowsy, as the driver's muscles become increasingly relaxed. (11,12) The gripping force signal is derived from a pressure sensor attached to the steering wheel, as shown in Fig. 9.…”
Section: Gripping Forcementioning
confidence: 99%
“…According to Lin et al (2007), the steering-wheel grip force is strongly correlated with other factors that are used to measure driver fatigue, such as the pulse wave [20]. Polychronopoulos et al (2004) suggested that the grip force can be used with other measures such as eye movement [21].…”
Section: Introductionmentioning
confidence: 99%
“…(2007) also developed driver fatigue detecting systems through a comprehensive multi-sensor driver-monitoring system that included the grip force [18], [20]- [21]. However, most previous studies focused on the development of measurement methods and did not verify the validity of the grip-force measure through empirical studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation